Analyzing the Metabolic Destiny of Potentilla discolor Bge. Extract and its Primary Components in Rat Models - Dang, Yanxin; Du, Menghan; Sun, Xiuxiu; Sun, Zeqi; Liu, Jie; Xie, Minzhen; Chen, Zhouxiu; Gu, Siqi; Wang, Qi; Liu, Guijun (Current Pharmaceutical Analysis, 2024)
BackgroundPotentilla discolor Bge. is a plant extensively utilized in Traditional Chinese Medicine (TCMs). Nevertheless, our knowledge of the chemical components and metabolic complexities in its extracts is still quite limited.ObjectiveThe study aimed to thoroughly analyze the flavonoid metabolism in Potentilla discolor Bge. extracts and conduct a pharmacodynamic evaluation.MethodsIn this study, we investigated the metabolism of flavonoids in Potentilla discolor Bge. extracts using SD rats. The research adopted the strategy of “in vivo metabolism assessment, basic study of pharmacodynamics and preliminary evaluation of molecular docking” to systematically investigate the pharmacodynamic substances and targets of action of Potentilla discolor Bge.ResultsThe results of the study showed that the main metabolic forms of Potentilla discolor Bge. in vivo include hydroxylation, methylation, and glycosylation. Among them, luteolin in the total flavonoids of Potentilla discolor Bge. has the strongest antimicrobial and antioxidant ability. Outcomes of molecular docking experiments indicated that the glycosylated metabolite of luteolin had a significant advantage in acting with Glp-1 (Glucagon-like peptide-1).ConclusionThe present study revealed the metabolic pathways of total flavonoids in Potentilla discolor Bge. It not only effectively screened out their pharmacodynamic substances and targets but also provided a theoretical basis for the application of TCMs into a systematic application and also provided ideas for the direction of drug optimization in the future. However, the sample range of this study is limited, and it generalizability needs to be investigated.
Keywords: Potentilla discolor bge.; flavonoids